Avaliação da atividade antiproliferativa e antiparasitária de constituintes isolados de Persea fulva (Lauraceae) - Reis, Isabella Mary Alves (2019)
The objective of this work was to carry out the phytochemical study and to evaluate the biological activities of Persea fulva (Lauraceae) extracts. Were isolated the unpublished compound (3E)-5,6-dihydro-5-(hydroxymethyl)-3-docdecylidenefuran-3(4H)-one, called majoranolide B, three γ-lactones known as majorenolide, majoranolide and majorynolide and a lignan, methylpiperitol. The structures were elucidated by spectroscopic analysis including 1D, 2D NMR (1H, 13C, 1H-1H-COZY, HMBC and HSQC) and LC-MS / MS. These compounds were screened for in vitro and in silico assays: antiproliferative in rat C6 glioma, anti-Leishmania and anti-T. cruzi activities. Majoranolide was the most active compound in all assays and showed an EC50 6.69 μM against cells of glioma C6, EC 50 of 2.9 ± 0.24 μM against trypomastigote forms of T. cruzi, EC50 of 36.7 ± 0.6 µM against promastigote forms of L. infantum. Methylpiperitol presented EC50 of 4.5 ± 1.1 µM against the trypomastigote forms of T. cruzi and EC50 of 4.1 ± 0.5 µM against the amastigote intracellular forms of L. infantum. In these assays, the selectivity index (SI) was established for all compounds and the results demonstrate that the compounds showed low toxicity to human cells and high selectivity to parasites. In silico assays confirm majoranolide as the most active compound based on the affinity energy values found. Thus, based on both in vitro and in silico results obtained for the isolated P. fulva compounds, it can be concluded that the species is a source of metabolites of interest with cytotoxic and antiparasitic activities.